Early Screening of Risk for Multidrug-Resistant Organisms in the Emergency Department in Patients With Pneumonia and Early Septic Shock: Single-Center, Retrospective Cohort Study. Issue 2 (February 2021) - Yiang, Giou-Teng; Tzeng, I-Shiang; Shui, Hao-Ai; Wu, Meng-Yu; Peng, Ming-Yieh; Chan, Chih-Yu; Chan, Edward D.; Wu, Yao-Kuang; Lan, Chou-Chin; Yang, Mei-Chen; Huang, Kuo-Liang; Wu, Chih-Wei; et al.
ABSTRACT: Objectives: Pneumonia is the fourth leading cause of death globally, with rapid progression during sepsis. Multidrug-resistant organisms (MDROs) are becoming more common with some healthcare-associated pneumonia events. Early detection of MDRO risk improves the outcomes; however, MDROs risk in pneumonia with sepsis is unknown. This study investigated the disease outcomes of pneumonia with septic shock in patients admitted in the emergency department (ED) intensive care unit (ICU), a population with a high prevalence of MDROs, after early screening of MDROs risk. Methods: In this retrospective cohort study, patients with pneumonia and early septic shock (n = 533) admitted to the ED at the Taipei Tzu Chi Hospital from 2013 to 2019 were selected. The study population was divided into four subgroups after the MDROs risk and screening procedure were completed within 1 or 6 h of admission. ICU mortality and multidrug antibiotic therapy were compared. Results: The high-risk MDROs groups had higher percentage of P aeruginosa than the low-risk group. Furthermore, the appropriate ED first antibiotics were higher in the 1-h subgroup than in the 6-h subgroup of the high-risk MDROs group. In multivariate analysis, the 6-h high-risk MDROs group had an adjusted odds ratio of 7.191 (95% CI: 2.911–17.767, P  < 0.001) and 2.917 (95% CI: 1.456–5.847, P  = 0.003) for ICU mortality and multidrug therapy in the ICU, respectively, after adjusting for other confounding factors. Conclusions: MDRO screening within 1 h is recommended following admission of patients with pneumonia and early septic shock in the ED, especially in areas with a high prevalence of MDROs. Abstract : Supplemental Digital Content is available in the text